2016
DOI: 10.1097/mao.0000000000001219
|View full text |Cite
|
Sign up to set email alerts
|

Single Institutional Experience With Observing 564 Vestibular Schwannomas

Abstract: Objective To characterize the risk and predictors of growth during observation of vestibular schwannomas (VS). Study Design Retrospective case series. Setting Single academic, tertiary care center. Patients 564 consecutive VS patients who underwent at least two MRI studies prior to intervention. Intervention(s) Serial MRI studies Main outcome measure(s) Tumor growth, defined as a ≥2 mm increase in the maximum tumor diameter between consecutive MRI studies, or between the first and last study. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
72
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 27 publications
11
72
1
2
Order By: Relevance
“…Our results do not show an association between aspirin intake and VS stability. This is in contrast to previously reported evidence of efficacy of aspirin in vitro as well as supporting observational data, but agree with those of one other similar large retrospective study . We demonstrated that the majority of patients would be able to take regular aspirin if found to be effective, with less than 10% being unable due to contraindications or high risk of gastrointestinal bleeding.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Our results do not show an association between aspirin intake and VS stability. This is in contrast to previously reported evidence of efficacy of aspirin in vitro as well as supporting observational data, but agree with those of one other similar large retrospective study . We demonstrated that the majority of patients would be able to take regular aspirin if found to be effective, with less than 10% being unable due to contraindications or high risk of gastrointestinal bleeding.…”
Section: Resultssupporting
confidence: 91%
“…These findings are in contrast to the previously reported evidence suggesting a potential mechanism and efficacy from in vitro studies, as well as a previously reported observational study . However, the results agree with one other similar large retrospective study by Hunter et al, which found that larger tumor size and disequilibrium at presentation were the only factors predictive of growth and not aspirin or other nonsteroidal anti‐inflammatory drug (NSAID) use …”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations